(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The purpose of this article is to offer a view on the subject of the perception of European consumers towards the foods containing genetically modified organisms (GMO). Furthermore, the article aims to identify patterns of influence of European legislation on biotechnology over the consumer’s perceptions and the role played bythe Public Administrations regarding the managing and controlling of genetic manipulationon foods.